Azacitidine treatment for patients with myelodysplastic syndrome and acute myeloid leukemia with chromosome 3q abnormalities. Issue 10 (14th July 2015) - Wanquet, Anne; Prebet, Thomas; Berthon, Céline; Sebert, Marie; Roux, Clémence; Kulasekararaj, Austin; Micol, Jean‐Baptiste; Esterni, Benjamin; Itzykson, Raphael; Thepot, Sylvain; Recher, Christian; Delaunay, Jacques; et al.
<x xml:space="preserve">Abstract</x> Acute Myeloid Leukemia (AML) and myelodysplasia (MDS) with chromosome 3q abnormalities have a dismal outcome either untreated or with conventional treatments. Azacitidine (AZA) is now considered as the standard of care in high‐risk MDS and oligoblastic AML patients. The objective of this study was to evaluate the impact of azacitine treatment in this cytogenetic subgroup. We report here a multicentre retrospective study of 157 patients treated with AZA for AML/MDS with chromosome 3q abnormalities and 27 patients with isolated EVI‐1 overexpression. Median age was 65 years, 40 patients (25%) had inv(3)(q21q26.2) or t(3;3)(q21;q26.2), 36 patients (23%) had other balanced 3q26 rearrangements, 8 patients (5%) had balanced 3q21 rearrangements and 73 patients (46%) had other 3q abnormalities. The overall response rate was 50% (29% CR). Median overall survival was 10.6 months. By multivariate analysis, patients with lower bone marrow blast counts, higher platelet counts, non‐complex cytogenetics, and absence of prior treatment with intensive chemotherapy had a better outcome. 27 patients were allo‐transplanted and achieved a 21‐month median OS. Balanced 3q21 translocations were associated with a better response rate and overall survival. Outcome of patients with isolated EVI‐1 overexpression was comparable to that of patients with chromosome 3q lesions. Thus, AML/MDS patients with 3q abnormalities appear to be a heterogeneous group in their response to AZA, and AZA may represent a suitable option in particular as a bridge to allogeneic transplantation. Am. J. Hematol. 90:859–863, 2015. © 2015 Wiley Periodicals, Inc.